SISTEM PEMBINAAN PRESTASI ATLET CABANG OLAHRAGA PANJAT TEBING FPTI (FEDERASI PANJAT TEBING INDONESIA) KOTA PEKANBARU - Heru Fiqram Amara; Ramadi Ramadi; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aims to find out the system of coaching the achievements of FPTI rock climbing athletes in Pekanbaru city. The research method used is quantitative descriptive research of 12 research subjects and based on a relatively small population is carried out with total sampling techniques. Instruments used in the form of interview techniques and questionnaires are conducted online. Based on the results of research and discussion that the author has outlined, from the test results of 10 athletes, it can be categorized as the level of the athlete achievement coaching system in the FPTI rock climbing sport of Pekanbaru city which is categorized very well 7 people by 70%, then in the good category there are 3 people by 30% and from the point of view of managers and coaches who are very good category with a score of 257 and a percentage score of 78.1%. The findings in this study from the point of view of managers and coaches there are obstacles in finding the seeds of athletes, financial limitations and limitations of facilities, infrastructure used by athletes in the training process.Key Words: Performance Coaching System.